2007
DOI: 10.1007/s10493-007-9117-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acaricides, pyrethroids and predator distributions on populations of Tetranychus urticae in apple orchards

Abstract: We sampled mites in three apple orchards in Nova Scotia, Canada, that had been inoculated with pyrethroid-resistant Typhlodromus pyri and had a history of Tetranychus urticae outbreaks. The objective of this study was to monitor populations of T. urticae and phytoseiid predators on the ground and in trees and to track dispersal between the two habitats. Pesticides were the chief cause of differences in mite dynamics between orchards. In two orchards, application of favourably selective acaricides (abamectin, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…Finally, there is the matter of ambulatory dispersal from one plot to the next. Firstly, both P. ulmi and T. pyri are absent or at very low numbers in orchard ground cover (Hardman et al 2007). As for T. urticae, numbers counted in ground cover quadrats were quite low, possibly because of control by N. fallacis, which was found in that habitat (unpublished data from this study).…”
Section: Mite Movements Between Plots In Adjacent Rowsmentioning
confidence: 70%
See 2 more Smart Citations
“…Finally, there is the matter of ambulatory dispersal from one plot to the next. Firstly, both P. ulmi and T. pyri are absent or at very low numbers in orchard ground cover (Hardman et al 2007). As for T. urticae, numbers counted in ground cover quadrats were quite low, possibly because of control by N. fallacis, which was found in that habitat (unpublished data from this study).…”
Section: Mite Movements Between Plots In Adjacent Rowsmentioning
confidence: 70%
“…The worst scenarios would occur where rates of ambulatory or aerial dispersal would be sufficient to induce strong correlations in mite counts in adjacent plots having different treatments, thereby obscuring the impact of the two factors that had most influence in this study: leaf chemistry and predation by phytoseiids. Risk factors could include the following: a strong contrast in tetranychid densities between trees in one plot and those in the neighbouring plot, particularly in early season; low densities of specialist phytoseiids such as N. fallacis in the ground cover, which would allow build up of T. urticae in that habitat, followed by higher immigration into trees; and low densities of phytoseiids such as T. pyri in trees, which would allow tetranychids moving into lower density plots more opportunity to multiply in the tree canopy (Hardman et al 2007). In these cases, use of larger plots with guard rows would be a wise precaution.…”
Section: Mite Movements Between Plots In Adjacent Rowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies related the negative effects of pesticides on Phytoseiidae (i.e. Kreiter et al, 1998;Childers et al, 2001;Chen et al, 2003;Hardman et al, 2006Hardman et al, , 2007Bonafos et al, 2008;Meyer et al, 2009;Peverieri et al, 2009). In surveys comparing treated and untreated apple orchards in North Carolina, Farrier et al (1980) showed that there were twofold more species on untreated trees compared to treated ones.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in apple orchards, the max. populations of spider mites usually occur in July and then decrease as a result of natural processes, as well as the activity of predatory mites or the use of selective pesticides (Hardman et al 2007;Duso et al 2009). Thus for late-season apple cultivars, in contrast to earlyseason varieties, harvesting can take place up to about 2-3 months after the max.…”
mentioning
confidence: 99%